Black pleural effusion caused by a pancreaticopleural fistula associated with autoimmune pancreatitis: A case report. Issue 36 (9th September 2022) - Miyadera, Keiki; Hisakane, Kakeru; Kato, Yuki; Atsumi, Kenichiro; Ono, Hiroki; Tanaka, Shu; Kubota, Kaoru; Seike, Masahiro; Gemma, Akihiko; Hirose, Takashi
Abstract : Rationale: Black pleural effusion is a rare medical condition and a diagnostic marker. Pancreaticopleural fistula is one of the causes of black pleural effusion. Thus far, black pleural effusions caused by pancreaticopleural fistulae have mostly been reported in patients with alcohol-induced chronic pancreatitis. In this report, we present a case of black pleural effusion caused by a pancreaticopleural fistula associated with autoimmune pancreatitis. Patient concerns and diagnosis: A 59-year-old female without a history of alcohol drinking presented to our hospital with a chief complaint of dyspnea, as well as chest and back discomfort. She had left pleural effusion, and thoracentesis showed black pleural effusion. Computed tomography revealed the presence of encapsulated fluid from the pancreatic tail to the left pleural cavity, which was diagnosed as a pancreaticopleural fistula. It also showed diffuse pancreatic swelling. Serum testing showed a high IgG4 level (363 mg/dL). These findings led to the diagnosis of autoimmune pancreatitis. Interventions and outcome: The patient underwent endoscopic pancreatic sphincterotomy and pancreatic duct stent placement and received treatment with steroids. After treatment, there was no further accumulation of pleural effusion observed. Conclusion: This is the first report of black pleural effusion due to a pancreaticopleural fistula associated with autoimmune pancreatitis. The characteristic appearance of black pleural effusion may assist diagnosis. We report this case to emphasize that autoimmune pancreatitis can be a cause of black pleural effusion.